Stratospheric and mesospheric HO2 observations from the Aura Microwave Limb Sounder - L. Millán; S. Wang; N. Livesey; D. Kinnison; H. Sagawa; Y. Kasai (Atmospheric Chemistry and Physics, 2015)
This study introduces stratospheric and mesospheric hydroperoxyl radical (HO2) estimates from the Aura Microwave Limb Sounder (MLS) using an offline retrieval (i.e. run separately from the standard MLS algorithm). This new data set provides two daily zonal averages, one during daytime from 10 to 0.0032 hPa (using day-minus-night differences between 10 and 1 hPa to ameliorate systematic biases) and one during nighttime from 1 to 0.0032 hPa. The vertical resolution of this new data set varies from about 4 km at 10 hPa to around 14 km at 0.0032 hPa. A description of the methodology and an error analysis are presented. Comparisons against the Whole Atmosphere Community Climate Model (WACCM), the Superconducting Submillimeter-Wave Limb-Emission Sounder (SMILES) and the Far Infrared Spectrometer (FIRS-2) measurements, as well as photochemical simulations, demonstrate the robustness of the retrieval and indicate that the retrieval is sensitive enough to detect mesospheric HO2 layers during both day and night. This new data set is the first long-term HO2 stratospheric and mesospheric satellite record and it provides needed constraints to help resolve the O3 deficit problem and the "HOx dilemma".